2011
DOI: 10.1021/ol2025229
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Properties of Boat-Shaped Glucopyranosyl Nucleic Acid

Abstract: A boat-shaped glucopyranosyl nucleic acid (BsNA) was synthesized to investigate the possibility that the lean of a nucleobase is a factor affecting duplex-forming ability of oligonucleotides. From the crystal structure of a BsNA nucleoside and the thermal stability of duplex oligonucleotides, it was found that not only the lean of the base but also the rotation angle of the glycosidic bond axis were important factors in a stable duplex formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…To explain the destabilizing behavior of the cANA incorporation, we speculated that the conformation of the cANA monomer in the duplex differs somewhat from that of Me-ANA. Recently, it has been suggested that very slight perturbations in the lean of the nucleobase or the rotation angle of the glycosidic bond axis can result in a large destabilizing effect . While the crystal structure of 15a suggests that a nearly perfect overlay with Me-ANA or HNA is possible, it is also likely that the addition of the 3′,5′-CH 2 O- bridge may introduce additional steric effects modifying the preferred conformation.…”
supporting
confidence: 70%
“…To explain the destabilizing behavior of the cANA incorporation, we speculated that the conformation of the cANA monomer in the duplex differs somewhat from that of Me-ANA. Recently, it has been suggested that very slight perturbations in the lean of the nucleobase or the rotation angle of the glycosidic bond axis can result in a large destabilizing effect . While the crystal structure of 15a suggests that a nearly perfect overlay with Me-ANA or HNA is possible, it is also likely that the addition of the 3′,5′-CH 2 O- bridge may introduce additional steric effects modifying the preferred conformation.…”
supporting
confidence: 70%
“…182 Expansion of the 2.2.1 ring system in LNA to a 2.2.2 ring system as exemplified by boat-shaped glucopyranosyl nucleic acid (bsNA) was also unsuccessful. 183 The poor result observed with the 2.2.2 scaffold was rationalized by changes in the lean of the base and the glycosidic torsion angles which presumably interferes with duplex formation. Interestingly, an analogue which represents the 2.2.2 version of α-L-LNA was slightly more successful but still less stabilizing as compared to α-L-LNA (Figure 14).…”
Section: ′-O-methoxyethyl Rna (Moe)mentioning
confidence: 99%
“…Expansion of the 2.2.1 ring system in LNA to a 2.2.2 ring system as exemplified by boat-shaped glucopyranosyl nucleic acid (bsNA) was also unsuccessful . The poor result observed with the 2.2.2 scaffold was rationalized by changes in the lean of the base and the glycosidic torsion angles which presumably interferes with duplex formation.…”
Section: Furanose Sugar Modificationsmentioning
confidence: 99%
“…The following TRPC3/C6/C7 activators were employed in the current study: L687 ( Supplementary Figure S1 , WO/2022/118966) ( 29 ), Cannabidiol (CBD) (#Axon1234; Axon Medchem, VA, USA), and GSK1702934A (#6508; Tocris Bioscience, Bristol, UK). SKF96365 (#1147/10; R&D Systems, MN, USA) was used as the TRPC channel inhibitor.…”
Section: Methodsmentioning
confidence: 99%